(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Pediatric renal stones may lead to pain, urinary obstruction, infection, and long-term renal damage. Although less common in children compared to adults, these stones remain a significant clinical problem. Objective: To evaluate and compare the effectiveness and safety of Mini-PCNL versus open pyelolithotomy in pediatric patients. Study design: A propective study . Duration and place of study. department of urology institute of kidney diseases Peshawar between 01-03-2021 and 31-06-2021 Methodology: This prospective analysis carried out at the Department of Urology, Khyber Teaching Hospital Peshawar, focused on pediatric patients diagnosed with kidney stones who had underwent either open pyelolithotomy or Mini percutaneous nephrolithotomy (Mini-PCNL) between 01-03-2021 and 31-06-2021 (study duration: 6 months). Patients of either gender aging 6 to 15 years with renal stones diagnosed on plain CT-KUB were enrolled. Efficacy and safety profile of both treatment modalities were compared. Results: Of the 61 patients who required intervention for the identified kidney stones in the pediatric patients, 40 underwent mini-PCNL while 21 underwent open pyelolithotomy. Age profile in mini-PCNL group averaged 11. 3 years and open pyelolithotomy group was 10. 8 years on average. The mini-PCNL group consisted of 25 patients of which 62. 5% were male patients while the open pyelolithotomy group had a total of 3 patients of which 66. 7% were male patients. The results obtained from the present study showed that the mini-PCNL group had a higher stone clearance rate of 95% as compared to the open pyelolithotomy group having a clearance rate of 90. 5%. Also, the cases that had mini-PCNL experienced fewer complication rates including haematuria, postoperative urinary tract infection, and fever than those who underwent open pyelolithotomy. Conclusion: Mini PCNL is a secure and efficient therapy substitute to open pyelolithotomy patients of paediatric age group diagnosed with renal calculi.